2020
DOI: 10.3390/jcm9072083
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Risk of Diabetic Complications in Novel Cluster-Based Diabetes Subgroups: A Japanese Retrospective Cohort Study

Abstract: Diabetes is a complex and heterogeneous disease, making the prediction of the risks of diabetic complications challenging. Novel adult-onset diabetes subgroups have been studied using cluster analysis, but its application in East Asians remains unclear. We conducted a retrospective cohort study to elucidate the clinical utility of cluster-based subgroup analysis in the Japanese population. Cluster analysis based on anti-glutamate decarboxylase antibody (GAD antibody) levels, age at diagnosis, body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
129
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(150 citation statements)
references
References 39 publications
17
129
1
3
Order By: Relevance
“…The proportion of the SIRD cluster ranged within 7.2% and 23.7% among studies, while 2 similar clusters were revealed by Safai et al such as insulin resistance with short disease duration (21.4%) and insulin resistance with long disease duration (31.7%) [7][8][9]14,[16][17][18]20]. The next most frequent cluster was MOD with varying percentages between studies from 20.4% to 34% [7][8][9]14,17,18,20]. The MARD cluster was the most prevalent among the mentioned five clusters in each study, falling within 34% and 45.4% [7][8][9]14,17,18,20].…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The proportion of the SIRD cluster ranged within 7.2% and 23.7% among studies, while 2 similar clusters were revealed by Safai et al such as insulin resistance with short disease duration (21.4%) and insulin resistance with long disease duration (31.7%) [7][8][9]14,[16][17][18]20]. The next most frequent cluster was MOD with varying percentages between studies from 20.4% to 34% [7][8][9]14,17,18,20]. The MARD cluster was the most prevalent among the mentioned five clusters in each study, falling within 34% and 45.4% [7][8][9]14,17,18,20].…”
Section: Resultssupporting
confidence: 65%
“…Liver diseases such as NAFLD and hepatic fibrosis were found to be associated with the SIRD cluster in studies of Zaharia et al and both studies of Ahlgvist et al [7,9,20] At the same time, neuropathies identified in the Zaharia et al study among SIDD individuals, were not associated with any cluster after adjustment for disease duration or age at onset in the study of Safai et al [9,16] In the study of Kahkoska et al, unadjusted analysis showed that CVDs were associated with the SIDD cluster, which is characterized by low BMI and insulin deficiency [14]. However, CVDs did not differ among clusters after adjustment for known modifiable and non-modifiable risk factors in the studies of Safai et al and Tanabe et al [8,16] Amato et al phenotyped diabetic patients based on fasting incretin levels into two independent clusters: cluster 1 (65.6%) with lower incretin levels and cluster 2 (34.4%) with higher incretin levels [10]. Thus, cluster 1 differed by a lower glucagon-like peptide-1 (GLP-1), glucose-dependent insulinotropic polypeptide (GIP) and, consequently, with higher levels of HbA1c and fasting plasma glucose (FPG) compared to cluster 2, which was explained by possible increased a-cell activity and its effect on the reduction in b-cell function.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations